Differences in mainland–island genetic diversity in two moths suggest species-specific outcomes - Sei-Woong Choi; Da-Hee Jin; Hyerin An; Kiwoong Nam; Bora Shin (PLoS ONE, 2026)
Genetic divergence along elevational gradients between mainland and island populations provides an opportunity to test the island genetic erosion model, which predicts reduced genetic diversity and increased differentiation in island populations. We examined two moth species, a geometrid moth ( Alcis angulifera ) and an erebid moth ( Hydrillodes morosa ), sampled along elevational gradients on Mt. Jirisan (mainland) and Mt. Hallasan (island) in southern South Korea. A total of 155 individuals were analyzed using mitochondrial cytochrome oxidase subunit I (mt COI) sequences. We identified 61 haplotypes across both species. A. angulifera exhibited similarly high genetic diversity on the mainland and island, whereas H. morosa showed overall lower diversity relative to A. angulifera but pronounced regional differences, with significantly higher haplotype and nucleotide diversity on the island. Mantel tests revealed significant genetic divergence between mainland and island populations but not within individual mountains, suggesting ongoing gene flow within elevational gradients. AMOVA indicated moderate differentiation in A. angulifera (F CT = 0.08) and stronger differentiation in H. morosa (F CT = 0.14), with most genetic variation occurring within populations. Gene flow estimates further highlighted contrasting patterns, with high connectivity in A. angulifera (Nm = 5.49) and restricted migration in H. morosa (Nm = 0.08). Together, these results indicate that while A. angulifera maintains genetic cohesion across regions, H. morosa exhibits stronger geographic and elevational structuring due to limited gene flow. Our findings do not support a universal reduction in genetic diversity in island populations; instead, they highlight the importance of species-specific ecological traits and geographic context in shaping genetic diversity patterns, suggesting that the island genetic-erosion pattern is more context-dependent than previously appreciated.